2013 6th International Congress on Image and Signal Processing (CISP) 2013
DOI: 10.1109/cisp.2013.6744044
|View full text |Cite
|
Sign up to set email alerts
|

A blind robust color image watermarking method using quaternion Fourier transform

Abstract: International audienceA blind color image watermarking scheme based on quaternion discrete Fourier transform (QDFT) and uniform log-polar mapping (ULPM) is proposed. In this scheme, a binary meaningful watermark is first embedded into the real part of QDFT coefficient of middle frequencies. In order to make it robust to geometric attacks, a bipolar binary watermark is inserted by the following ULPM method. This second watermark can resist geometric attacks and is used so as to invert such a transformation. Onc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 8 publications
0
10
0
Order By: Relevance
“…A semi-blind scheme that combines quaternion singular value decomposition and QDFT was presented by Sun et al [13]. Recently, Chen et al [14] demonstrated how to fully utilize the 4-D quaternion frequency domain in order to embed a large capacity color image watermark in the case of the well-known quantization index modulation (QIM) [14][15][16]. Wang et al [15] developed a QDFT-based blind color image watermarking algorithm where least squares support vector machine (LS-SVM) were combined with pseudo-Zernike moments to resist geometric attacks.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A semi-blind scheme that combines quaternion singular value decomposition and QDFT was presented by Sun et al [13]. Recently, Chen et al [14] demonstrated how to fully utilize the 4-D quaternion frequency domain in order to embed a large capacity color image watermark in the case of the well-known quantization index modulation (QIM) [14][15][16]. Wang et al [15] developed a QDFT-based blind color image watermarking algorithm where least squares support vector machine (LS-SVM) were combined with pseudo-Zernike moments to resist geometric attacks.…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al [15] developed a QDFT-based blind color image watermarking algorithm where least squares support vector machine (LS-SVM) were combined with pseudo-Zernike moments to resist geometric attacks. In [16], a blind color image watermarking method was proposed to resist geometric attacks by combining the uniform log-polar mapping (ULPM) with QDFT.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Quaternions (or hypercomplex) have been widely used in geometry and physics since born, and quaternions are introduced to the field of color image processing in recent years [6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24]. Gray image encryption method mostly proceed in airspace which has little operating space and low security factor, so the improved encryption method is performed in the frequency domain, and orthogonal transformation commonly used are discrete Cosine transform (DCT), discrete Fourier transform (DFT) and discrete wavelet transform(DWT), etc.…”
Section: Introductionmentioning
confidence: 99%
“…Ell was the first person who gave the definition of quaternion (hypercomplex) Fourier transform (QFT) in his doctoral thesis [6], Bahri and Ashino introduced the correlation theorem of QFT form II [7], then Sangwine applied QFT to color images, and gave the definition of quaternion discrete Fourier transform (QDFT) [8]. Ouyang and Wen et al, applied QFT to color image watermarking, and proposed a robust blind color image watermarking algorithm [9]. GAI and Wang et al combined DQFT and double random phase encryption technology based on optical image encryption theory, proposing a new double random phase encryption technology for color images [10][11].…”
Section: Introductionmentioning
confidence: 99%